1995
DOI: 10.1080/00207599508246973
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Right Wing Authoritarianism Scale in Black and White South African Students

Abstract: Recently Taylor and Boeyens (1991) showed that the South African Personality Questionnaire has inadequate internal consistency and factorial validity for use in the black population. This paper reports a study supporting their conclusion that scales developed with data from a white sample do not hold together psychometrically or conceptually when used with a black sample. In a sample of white students, Altemeyer's Right Wing Authoritarianism scale, initially developed in Canada, had an acceptable alpha of 0.83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…It is not uncommon for a researcher to use a scale developed in one country to gather data in another, on the assumption that the scale would be measuring the same construct in its new area of application. Edwards & Leger (1995) list various studies in which this has been done by researchers in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…It is not uncommon for a researcher to use a scale developed in one country to gather data in another, on the assumption that the scale would be measuring the same construct in its new area of application. Edwards & Leger (1995) list various studies in which this has been done by researchers in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1994, there have been few studies in South Africa that have focused spe cifically on the psychometric properties of measures of right-wing authoritarianism. A notable exception is a study by Edwards and Leger (1995) that examined the psychometric properties of Altemeyer's (1981) RWA scale in both black and white South African samples. These authors found that this scale showed acceptable levels of reliability and validity in white samples, but did not hold together either psychometrically or conceptually when used in a black sample.…”
mentioning
confidence: 99%
“…The problems of using European and North American instruments in research in Africa and in South Africa in particular have been widely discussed (Edwards & Leger, 1995;Edwards & Riordan, 1994;Taylor & Booyens, 1991). Even where respondents speak English regularly and receive their education in this language, some common terms may not be familiar to them or may have different connotative meanings.…”
Section: Discussionmentioning
confidence: 99%
“…laxatives, diuretics and binge) were unfamiliar to males and particularly to black males. Although tests vary in their robustness, most tests developed in Europe and North America show differentpsychometric characteristics when administered to black respondents in South Africa (Edwards & Leger, 1995;Edwards & Riordan, 1994;Taylor & Booyens, 1991). Because ofdifferences in the connotative meaning ofcertain words and phrases, correlations between individual items may be lower and, as a result, internal consistency as measured by the coefficient is typical lower.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation